2014
DOI: 10.1111/jgh.12776
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of angiogenesis in Helicobacter heilmannii‐induced mucosa‐associated lymphoid tissue lymphoma: Interaction with c‐Met and hepatocyte growth factor

Abstract: Background and Aim: The hepatocyte growth factor (HGF)/c-Met pathway has attracted attention in the formation of malignant tumors, as HGF secreted from the microcirculatory components as well as residing macrophages has been suggested to act on the c-Met receptors of cancer cells to decrease apoptosis and increase proliferation, invasion, and metastasis. The present study was undertaken to elucidate the interaction of the gastric, hepatic, and pulmonary mucosa-associated lymphoid tissue (MALT) lymphoma induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…The efficacy of traditional herbal medicines in the treatment of FD has also been reported . For example, we conducted a multicenter, randomized, placebo‐controlled, parallel‐group trial to investigate the effect of rikkunshito, a traditional Japanese herbal medicine, on FD . In this study, especially, epigastric pain was improved in the rikkunshito group.…”
Section: Management and Treatment Of Fdmentioning
confidence: 97%
See 1 more Smart Citation
“…The efficacy of traditional herbal medicines in the treatment of FD has also been reported . For example, we conducted a multicenter, randomized, placebo‐controlled, parallel‐group trial to investigate the effect of rikkunshito, a traditional Japanese herbal medicine, on FD . In this study, especially, epigastric pain was improved in the rikkunshito group.…”
Section: Management and Treatment Of Fdmentioning
confidence: 97%
“…Membrane‐binding assay analysis has revealed that acotiamide has binding affinity with muscarinic M 1 and M 2 , but not M 3 receptors . Acotiamide has antagonistic effects on M 1 and M 2 receptors . M 3 receptors are expressed in the stomach and stimulate gastric motility.…”
Section: Acotiamide: a Novel Prokinetic Agentmentioning
confidence: 99%
“…c-MET was found in the lymphocytes composing mucosa-associated lymphoid tissue (MALT) lymphoma, and HGF was recognized mostly in the endothelial cells and macrophages in the MALT lymphoma [41]. HGF activator was localized on the mesenchymal cells other than the lymphocytes.…”
Section: The Expression/activation Of Hgf/c-met In Different Types Ofmentioning
confidence: 99%
“…HGF activator was localized on the mesenchymal cells other than the lymphocytes. c-MET inhibition suppressed the hepatic and pulmonary MALT lymphoma, while the gastric MALT lymphoma showed only a tendency to decrease in size [41]. …”
Section: The Expression/activation Of Hgf/c-met In Different Types Ofmentioning
confidence: 99%
See 1 more Smart Citation